Evaluation of oral health-related quality of life among institutionalized orphan children - K L Girish Babu; Gururaj Hebbar Kavyashree (Wolters Kluwer Medknow Publications, 2021)
Introduction: Children residing in orphanages are a disadvantaged section of the population. Inadequate care can impair the quality of life of orphan children. Aim: The aim of this study was to assess the oral health-related quality of life and dental caries status among institutionalized orphan children. Materials and Methods: Children without parents, aged 6-14 years, were selected from government-run orphanages. Children who were willing to participate were included. Data on oral health-related quality of life were collected by personal interviews by a single investigator. Following, intraoral examination of each child was carried out in an adequate natural light using a sterilized mouth mirror and probe. Dental caries was assessed according to the World Health Organization criteria. The data obtained were subjected to statistical analysis. Results: The Decayed, Missed and Filled teeth (DMFT) score of males was 0.41 ± 0.86 and females was 0.97 ± 1.44, and the difference was statistically significant. The mean of oral symptoms, functional limitation, emotional well-being, and social well-being was 26.49 ± 4.48, 37.75 ± 3.63, 33.31 ± 4.18, and 47.92 ± 3.37, respectively. Conclusions: The prevalence of dental caries was low among these orphan children. The quality of life of these children was not affected by their dental caries status.